IMPLEMENTASI MEDIA PEMBELAJARAN ARTICULATE STORYLINE 3 BERBASIS CONTEXTUAL EKOPEDAGOGIK DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII DI SMP CITRA ALAM - Sari, Jessika Nacha; Safitri, Desy; Saipiatuddin, Saipiatuddin (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The success of a learning can be measured by looking at the abilities possessed by students through learning processes and experiences. The reality that occurs at Citra Alam Junior High School in Grade VIII teachers tend to use simple powerpoints without interactive, causing students to be passive, using lecture methods, lack of association with current issues and the use of interactive games have an impact on learning outcomes, so that students' scores have not reached the Minimum Completeness Criteria (KKM) score. This study discusses how the implementation of Articulate Storyline 3 learning media based on ecopedagogic contextual in social studies learning outcomes of grade VIII students at Citra Alam Junior High School. This type of research is a Class Action Research (PTK) which is carried out for two cycles. The subjects of this study are 10 students in grade VIII. Data collection is carried out through tests and non-tests. The results of the study show that the Articulate Storyline 3 learning media has succeeded in improving social studies learning outcomes of students. This is evident from the percentage of learning outcomes in cycle one of 40% with an average score of 70 and the results of students' activeness show that they are less active in answering. Then it increased in the second cycle with a percentage of 90% with an average score of 94 which showed that the percentage of active and very active students increased. ABSTRAK Keberhasilan suatu pembelajaran dapat diukur dengan melihat kemampuan yang dimiliki oleh peserta didik melalui proses dan pengalaman belajar. Realita yang terjadi di SMP Citra Alam di Kelas VIII guru cenderung menggunakan powerpoint sederhana tanpa interaktif menyebabkan peserta didik bersikap pasif, menggunakan metode ceramah, minimnya pengaitan dengan isu terkini dan penggunaan game interaktif berdampak pada hasil belajar, Sehingga nilai peserta didik belum mencapai nilai Kriteria Ketuntasan Minimum (KKM). Penelitian ini membahas tentang bagaimana implementasi media pembelajaran Articulate Storyline 3 berbasis contextual ekopedagogik dalam hasil belajar IPS peserta didik kelas VIII di SMP Citra Alam. Jenis penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan selama dua siklus. Subjek Penelitian ini adalah peserta didik kelas VIII berjumlah 10 siswa. Pengumpulan data dilakukan melalui tes dan non tes. Hasil penelitian menunjukan bahwa media pembelajaran Articulate Storyline 3 berhasil meningkatkan hasil belajar IPS peserta didik. Hal ini terbukti dari persentase hasil belajar pada siklus satu sebesar 40% dengan rata-rata nilai 70 dan hasil keaktifan peserta didik menunjukan kurang aktif dalam berpendapat. Kemudian meningkat pada siklus kedua dengan persentase 90% dengan rata-rata nilai 94 yang hasil keaktifan peserta didik menunjukan persentase peserta didik yang aktif dan sangat aktif meningkat.